2017
DOI: 10.1530/jme-17-0020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NMB, GRP and their receptors (BRS3, NMBR and GRPR) in chickens

Abstract: The two structurally and functionally related peptides, gastrin-releasing peptide (GRP) and neuromedin B (NMB) play critical roles in many physiological/pathological processes in mammals. However, the information regarding the expression and functionality of avian NMB, GRP and their receptors is limited. Here, we characterized cNMB, cGRP and their receptors (cNMBR, cGRPR and cBRS3) in chickens. Our results showed that: (1) cNMBR and cGRPR expressed in CHO cells could be potently activated by cNMB and cGRP, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 74 publications
4
20
0
Order By: Relevance
“…Under positive selection, with three altered key residues (R127Q, S205P, and H294R) affecting ligand binding and activation, placental mammalian BRS3 lost connection with its original ligands and became constitutively regulated by its altered G protein selectivity barcodes and its altered N terminus, which also underwent positive selection in placental mammals (Figs 3–6). Therefore, our results showed that the cognate ligand-BLPs for BRS3 actually are NMB and GRP, but only in nonplacental vertebrates, including nonplacental mammals (Marsupialia and Monotremata) (Fig 2, Fig 3 and S4 Fig), which is consistent with previous study [47]. In contrast, placental mammalian BRS3 underwent positive selection to become a constitutive active GPCR in a ligand-independent manner (Fig 2, Fig 3 and S4 Fig).…”
Section: Discussionsupporting
confidence: 91%
“…Under positive selection, with three altered key residues (R127Q, S205P, and H294R) affecting ligand binding and activation, placental mammalian BRS3 lost connection with its original ligands and became constitutively regulated by its altered G protein selectivity barcodes and its altered N terminus, which also underwent positive selection in placental mammals (Figs 3–6). Therefore, our results showed that the cognate ligand-BLPs for BRS3 actually are NMB and GRP, but only in nonplacental vertebrates, including nonplacental mammals (Marsupialia and Monotremata) (Fig 2, Fig 3 and S4 Fig), which is consistent with previous study [47]. In contrast, placental mammalian BRS3 underwent positive selection to become a constitutive active GPCR in a ligand-independent manner (Fig 2, Fig 3 and S4 Fig).…”
Section: Discussionsupporting
confidence: 91%
“…Based on the cloned cDNAs of tilapia MC4R and MRAP2b, the coding regions of these genes were amplified by PCR with high-fidelity Taq DNA polymerase and cloned into pcDNA3.1 (+) vector. According to our established method, tilapia MC4R transiently expressed in CHO cells was treated by synthetic tilapia ACTH/α-MSH/β-MSH (10 −10 to 10 −9 M, 6 h), and then, the receptor-activated cAMP signaling pathway was monitored by a pGL3-CRE-Luciferase reporter system, which is capable of monitoring the receptor-mediated cAMP level [28,55]. To test whether tilapia MRAP2b could alter the pharmacological property of tilapia MC4R, CHO cells co-transfected with MRAP2 and receptor expression plasmids were treated by tilapia ACTH, α-MSH, and β-MSH, and the relative potencies of the three peptides in activating MC4R were evaluated by the mentioned reporter system [28,55].…”
Section: Functional Analysis Of Timc4r and Timrap2bmentioning
confidence: 99%
“…Bombesin-like receptor 3 (BRS-3) is an orphan G protein-coupled receptor (GPCR), first identified via sequence similarity to the gastrin releasing peptide and neuromedin B receptors [3] , [4] , [5] . To date, attempts to identify a mammalian endogenous BRS-3 ligand have been unsuccessful [6] , [7] , [8] , [9] , although in chicken and spotted gar (a fish), gastrin releasing peptide and neuromedin B both appear to be endogenous ligands [10] . Mammalian BRS-3 may be conserved during evolution because it can modify the response pattern of other GPCRs or contribute to basal signaling [11] .…”
Section: Introductionmentioning
confidence: 99%